Portable electronics queue control system - Wong, Chun Yuan (2012)
A queue control system is developed to control the queue in businesses and in servicing counters. By using queue control system, the company or service provider will be able to control the queue of the customers and ensure the provision of a better service. Due to the increase of the demand from people for a better service, it is more likely that a queue control system is required to be allocated at all time for all companies. However, looking the queue control systems currently available in the market, most of them are big in size and unable to be moved here and there. These portable queue systems are mainly connected to big screen or static panel at the entrance for customers to obtain their numbers. This will cause problem in moving counters such as ticketing counters outdoor or servicing counters in a shopping mall. Hence, there is a demand for the portable queue control system which is able to be moved here and there. The purpose of this project is to develop a portable queue control system which is able to fulfill the request discussed above. Looking alike as the normal queue control system, portable queue control system is a small-sized system which can be used to control queue during outdoor events. Unlike static queue control system, portable queue control system is able to function in small range using 9V battery and is convenient to be carried here and there. In this simple system, one push button will be allocated at the display panel, allowing customer to input their arrivals, and a push button will be used to allow the counters to call for the next customer to be served. The display panel and the counters will be communicating with each other via XBEE wireless communication. For further enhancement, the system will be able to control the absence of more customers and sound notification which will call out the customer number and counter number is able to be installed. Besides that, duplication of the display can be made and the multi segments which are big in size can be used.